Kærlighed og seksualitet i markedsperspektiv - Petersen, Hanne (Samfundsøkonomen, 2014)
»Along with the growth of marriage and sex markets at the global and European level, sexualities and intimacies as well as traditional conceptions of the institution of marriage and family have come to the fore.« (Saarinen & Calloni, 2012: 12)